Development of a Sigi Cultural Ethnomathematics-Based Student Learning Needs Questionnaire to Support SDG 4: Quality Education - Mailili Wahyuni H; Jamhari Mohammad; Ratman Ratman; Astija Astija (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To develop a valid and reliable questionnaire and teacher interview instrument for assessing students’ learning needs and characteristics in junior high schools in Sigi Regency, and to analyze these needs as a basis for developing Sigi culture-based ethnomathematics teaching materials. Method: The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Development, and Dissemination). Instrument development involved needs analysis, instrument design, expert validation, empirical testing, and reliability analysis. Results: Expert validation indicated that the instruments were feasible for use with minor revisions. Empirical testing showed that 17 of 26 questionnaire items and 11 of 15 interview questions were valid. Reliability analysis produced coefficients of 0.786 for the questionnaire and 0.798 for the interview guideline, indicating good reliability. Novelty: Developing and validating a student learning needs questionnaire specifically designed to support the development of Sigi cultural ethnomathematics-based mathematics teaching materials. By integrating students’ learning needs with local cultural contexts, the instrument provides a systematic framework for designing culturally responsive mathematics instruction that contributes to SDG 4 (Quality Education) through inclusive, contextual, and meaningful learning while supporting the preservation of local cultural heritage in line with SDG 11 (Sustainable Cities and Communities).